Severe Amitriptillin Intoxication Treated with Intravenous Lipid Emulsion - Ayyüce Ünlü; Mehmet Alakaya; Sadık Kaya; Ali Ertuğ Arslankoylu; Ali Korulmaz (Galenos Yayinevi, 2021)
Intoxication with tricyclic antidepressant drugs causes serious toxic findings even at low doses. Despite common use of the antidepressant drugs, there are no randomized controlled trials about treatments in tricyclic antidepressant drug intoxication. Here we report a 23-month-old girl admitted to the emergency room with status epilepticus. We diagnosed that she had ingested toxic amount of amitriptillin. Since the patient's clinical status deteriorated despite conventional treatments (lidocaine, epinephrine, norepinephrine, magnesium sulphate, sodium bicarbonate, activated charcoal), we administered intravenous lipid emulsion and treated the patient successfully.